Lack of Association between Toxocara Exposure and Suicide Attempts in Psychiatric Patients - Alvarado-Esquivel, Cosme (J Parasitol Res, 2015)
Infection with Toxocara may affect the central nervous system. A high seroprevalence of Toxocara infection has been reported in psychiatric patients. To the best of our knowledge, there is no previous report about an association of Toxocara infection with suicide attempts. Therefore, we sought to determine whether Toxocara exposure is associated with suicide attempts in psychiatric patients. We studied 282 psychiatric outpatients (156 with suicide attempts and 126 without suicide attempts). Sera of patients were analyzed for the presence of anti-Toxocara IgG antibodies by using a commercially available enzyme immunoassay. One of the 156 (0.6%) suicide attempters and 1 (0.8%) of the 126 controls were positive for anti-Toxocara IgG antibodies (OR = 0.80; 95% CI: 0.04–13.02; P = 1.00). Toxocara seropositivity was significantly higher (P = 0.01) in male patients with consumption of raw dried goat meat than male patients without this consumption. Results suggest that Toxocara exposure is not associated with suicide attempts in psychiatric outpatients in Durango City, Mexico. However, further studies with larger samples sizes to confirm our results should be conducted. Too few patients were seropositive to assess further associations of Toxocara exposure with sociodemographic, clinical, and behavioral characteristics of the psychiatric patients.